Synthesis of aluminum-containing CIT-13 and CIT-15 molecular sieves

By preparing and processing a reaction mixture containing aluminum, silicon and germanium, aluminium germanium silicate molecular sieve CIT-13 and CIT-15 are formed, which solves the problem of insufficient catalytic activity and significantly improves the catalysis of these molecular sieves during hydrocarbon conversion process performance.

CN119173477APending Publication Date: 2024-12-20CHEVRON USA INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380039218.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-09
Filing Date
2023-05-08
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The catalytic activity of germanium silicate molecular sieves CIT-13 and CIT-15 is insufficient to be suitable for certain hydrocarbon conversion processes, mainly because it is difficult to effectively incorporate aluminum atoms into these molecular sieve backbones.

Method used

Aluminum germanium silicate molecular sieve CIT-13 and CIT-15 were prepared by a method, by preparing the reaction mixture including aluminum source, silicon source, germanium source, organic structure guide agent, fluoride ion source and water, and under specific conditions It forms crystallization, which is subsequently calcined and processed to form a catalytically active aluminum germanium silicate molecular sieve.

Benefits of technology

The successful introduction of aluminum into the CIT-13 and CIT-15 frameworks has improved the catalytic activity of these molecular sieves, especially in the process of hydrocarbon conversion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005124577240000051
    Figure BDA0005124577240000051
  • Figure BDA0005124577240000061
    Figure BDA0005124577240000061
  • Figure FDA0005124577220000011
    Figure FDA0005124577220000011
Patent Text Reader

Abstract

The present invention provides a process for preparing molecular sieves CIT-13 and CIT-15 incorporating aluminum in the framework structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for preparing aluminum germanosilicate molecular sieves CIT-13 and CIT-15. Background Art

[0002] Molecular sieves are a commercially important class of materials that possess a unique crystal structure with a defined pore structure as evidenced by a unique X-ray diffraction (XRD) pattern and have a specific chemical composition.

[0003] Molecular sieves are classified by the International Zeolite Association Structure Commission according to the rules of the IUPAC Zeolite Nomenclature Commission. According to this classification, framework zeolites and other crystalline microporous crystalline materials of determined structure are assigned a unique three-letter code and are described, for example, in "Atlas of Zeolite Framework Types" (Elsevier, Sixth Revised Edition, 2007).

[0004] *CTH framework type molecular sieves are disordered materials having a two-dimensional pore system with pores bound by 14-membered rings and 10-membered rings. *Examples of CTH framework type molecular sieves include the germanosilicates CIT-13, NUD-2, and SAZ-1. Extra-large-pore molecular sieves such as CIT-13 have attracted interest due to their ability to catalyze reactions of larger reactant and product molecules.

[0005] The germanosilicate CIT-13 consists of silicon-rich CFI layers bridged by two-dimensional arrays of germanium-rich double 4-ring (D4R) units. The instability of the Ge-rich D4R units in the CIT-13 germanosilicate provides a rich chemical property that varies depending on the germanium content in the CIT-13 composition. U.S. Patent Application Publication No. 2017 / 0252729 discloses the topological transformation of the germanosilicate CIT-13 to CIT-15, a molecular sieve material having a one-dimensional pore system with ten-membered ring pores. Molecular sieves with one-dimensional ten-membered ring pores exhibit attractive properties as catalysts or catalyst components for the dewaxing of hydrocarbon feedstocks.

[0006] However, the catalytic activity of germanosilicate molecular sieves (such as CIT-13 and CIT-15) is not sufficient to be suitable for certain hydrocarbon conversion processes. An important synthetic challenge is to incorporate catalytically active sites (such as aluminum atoms) into the framework of these molecular sieves.

[0007] Thus, provided herein are methods for introducing aluminum into the framework of CIT-13 and CIT-15. Summary of the invention

[0008] In one aspect, a method for synthesizing an aluminum germanosilicate molecular sieve CIT-13 is provided, the method comprising: (1) preparing a reaction mixture, the reaction mixture comprising: (a) an aluminum source; (b) a silicon source; (c) a germanium source; (d) an organic structure directing agent (Q), the organic structure directing agent comprising one or more of a 1,2-dimethyl-3-(3-methylbenzyl)imidazolium cation, a 1-methyl-3-(3-methylbenzyl)-imidazolium cation, a 1,2-dimethyl-3-(3,5-dimethylbenzyl)imidazolium cation and a 1-methyl-3-(3,5-dimethylbenzyl)-imidazolium cation; (e) a fluoride ion source; (f) water; and (g) a seed material, wherein the seed material comprises a crystalline molecular sieve of a *CTH framework type; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form aluminum germanosilicate molecular sieve crystals.

[0009] In another aspect, a method for synthesizing aluminum germanium silicate molecular sieve CIT-15 is provided, the method comprising the following steps: (1) preparing a reaction mixture, the reaction mixture comprising: (a) an aluminum source; (b) a silicon source; (c) a germanium source; (d) an organic structure directing agent (Q), the organic structure directing agent comprising one or more of 1,2-dimethyl-3-(3-methylbenzyl)imidazolium cation, 1-methyl-3-(3-methylbenzyl)-imidazolium cation, 1,2-dimethyl-3-(3,5-dimethylbenzyl)imidazolium cation and 1-methyl-3-(3,5-dimethylbenzyl)-imidazolium cation; (e) a fluoride ion source; (f) f) water; and (g) seed material, wherein the seed material comprises a crystalline molecular sieve of *CTH framework type; (2) subjecting the reaction mixture to crystallization conditions sufficient to form aluminum germanosilicate molecular sieve crystals; (3) recovering and calcining the product of step (2) to obtain a calcined aluminum germanosilicate CIT-13 molecular sieve; (4) treating the calcined aluminum germanosilicate CIT-13 molecular sieve with water under conditions sufficient to degermanate at least a portion of the calcined aluminum germanosilicate CIT-13 molecular sieve to obtain a phyllosilicate comprising a stratified cfi layer; and (5) recovering and calcining the phyllosilicate under conditions sufficient to convert the phyllosilicate into an aluminum germanosilicate CIT-15 molecular sieve. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 is the powder X-ray diffraction (XRD) pattern of the Al-CIT-13 sample prepared in Example 1.

[0011] Figure 2 is a scanning electron microscope (SEM) image of the Al-CIT-13 sample prepared as in Example 1.

[0012] Figure 3is the powder XRD pattern of the Al-CIT-15 sample prepared in Example 5.

[0013] Figure 4 is a SEM image of the Al-CIT-15 sample prepared as in Example 5.

[0014] Figure 5 is a graph of conversion or yield versus temperature for the hydroconversion of n-decane using a Pd-exchanged Al-CIT-15 catalyst.

[0015] Figure 6 is a graph of yield versus conversion for n-decane hydrogenation using a Pd-exchanged Al-CIT-15 catalyst.

[0016] Figure 7 is a graph showing a plot of iso-C10 product distribution for n-decane hydroconversion using a Pd-exchanged Al-CIT-15 catalyst. DETAILED DESCRIPTION

[0017] Glossary

[0018] The term "aluminogermanosilicate" means a zeolite having a framework composed of aluminum oxide, germanium oxide and silicon dioxide (ie, repeating AlO4, GeO4 and SiO4 tetrahedral units).

[0019] The term "framework type" is used in the sense described in "Atlas of Zeolite Framework Types" by Ch. Baerlocher, LB McCusker and DH Olson (Elsevier, 6th revised edition, 2007).

[0020] The term "sol" means a dispersion of colloidal (ie, less than one micron in size) solid particles in a liquid.

[0021] The term "SiO 2 / Al 2 O 3 "Molar ratio" can be abbreviated as "SAR".

[0022] Synthesis of Aluminum Germanium Silicate CIT-13 (Al-CIT-13)

[0023] The aluminum germanosilicate molecular sieve CIT-13 can be synthesized by the following steps: (1) preparing a reaction mixture, the reaction mixture comprising: (a) an aluminum source; (b) a silicon source; (c) a germanium source; (d) an organic structure directing agent, the organic structure directing agent comprising one or more of 1,2-dimethyl-3-(3-methylbenzyl)imidazolium cation, 1-methyl-3-(3-methylbenzyl)-imidazolium cation, 1,2-dimethyl-3-(3,5-dimethylbenzyl)imidazolium cation and 1-methyl-3-(3,5-dimethylbenzyl)-imidazolium cation; (e) a fluoride ion source; (f) water; and (g) a seed material, wherein the seed material comprises a crystalline molecular sieve with a *CTH framework topology structure; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form aluminum germanosilicate molecular sieve crystals.

[0024] The reaction mixture may have a molar ratio composition within the range shown in Table 1:

[0025] Table 1

[0026] Reactants The most extensive typical <![CDATA[(SiO 2 +GeO 2 ) / To 2 OR 3 ]]> 35 to 500 50 to 165 <![CDATA[Q / (SiO 2 +GeO 2 )]]> 0.20 to 0.75 0.25 to 0.65 <![CDATA[F / (SiO 2 +GeO 2 )]]> 0.20 to 0.75 0.25 to 0.65 <![CDATA[H 2 O / (SiO 2 +GeO 2 )]]> 5 to 20 5 to 15

[0027] Suitable aluminum sources include hydrated aluminum oxide, aluminum hydroxide, alkali metal aluminates, aluminum alkoxides (eg, aluminum isopropoxide), and water-soluble aluminum salts (eg, aluminum nitrate).

[0028] Suitable silicon sources include colloidal silica, fumed silica, alkali metal silicates (eg, sodium silicate), tetraalkyl orthosilicates (eg, tetraethyl orthosilicate), and precipitated silica.

[0029] A combined aluminum source and silicon source, such as an aluminosilicate sol, may also be used. Suitable aluminosilicate sols are available from NALCO Water, a subsidiary of Ecolab. Aluminosilicate sols may be used as the sole or primary silicon and aluminum source. The term "primary" means greater than 50 mole % (e.g., greater than 75 mole % or greater than 90 mole %).

[0030] Suitable germanium sources include germanium oxide, germanium nitrate, and tetraalkoxygermanium compounds (eg, tetraethoxygermanium).

[0031] In some aspects, silicon oxide and germanium oxide are present in an SiO2 ratio in the range of 1 to 10 (e.g., 3 to 8). 2 / GeO 2 The molar ratio exists in the reaction mixture.

[0032] The organic structure directing agent (Q) includes one or more of 1,2-dimethyl-3-(3-methylbenzyl)imidazolium cation, 1-methyl-3-(3-methylbenzyl)-imidazolium cation, 1,2-dimethyl-3-(3,5-dimethylbenzyl)imidazolium cation and 1-methyl-3-(3,5-dimethylbenzyl)-imidazolium cation, which are represented by the following structures (1), (2), (3) and (4), respectively:

[0033]

[0034]

[0035] Suitable sources of Q include hydroxides, chlorides, bromides and / or other salts of the relevant quaternary ammonium compounds.

[0036] Suitable fluoride ion sources include HF, NH 4 F and NH 4 HF 2 .

[0037] The seed material may include any molecular sieve material having a *CTH type framework structure. The seed material may include a molecular sieve selected from the group consisting of CIT-13, NUD-2, SAZ-1, and any combination thereof. In some aspects, the seed material includes CIT-13. The seed material may be added in an amount of 0.1 to 10% of the weight of silica used in the reaction mixture.

[0038] The reaction mixture can be prepared by any conceivable means, wherein mixing is preferably carried out by agitation, preferably by stirring. The reaction mixture can be prepared in batch, continuous or semi-continuous mode.

[0039] The reaction mixture may be in the form of a solution, a colloidal dispersion, a gel or a paste, with a gel being preferred.

[0040] The crystallization of the desired molecular sieve from the reaction mixture can be carried out under static or stirred conditions in a suitable reactor vessel, such as, for example, a polypropylene can or a Teflon-lined or stainless steel autoclave placed in a convection oven maintained at a temperature of 100° C. to 200° C. for a period of time sufficient for crystallization to occur (e.g., about 1 day to 30 days, or 1 day to 15 days). Crystallization is typically carried out under autogenous pressure.

[0041] Once the desired molecular sieve crystals are formed, the solid product can be separated from the reaction mixture by standard mechanical separation techniques (such as centrifugation or filtration). The recovered crystals are washed with water and then dried for a few seconds to a few minutes (e.g., 5 seconds to 10 minutes for rapid drying) or a few hours (e.g., 4 hours to 24 hours for oven drying at 75° C. to 150° C.) to obtain the initial synthesis molecular sieve crystals. The drying step can be performed under vacuum or atmospheric pressure.

[0042] As a result of the crystallization process, the recovered as-synthesized crystalline molecular sieve product contains within its pore structure at least a portion of the organic structure directing agent used in the synthesis.

[0043] The organic structure directing agent can be removed by calcination, wherein the as-synthesized molecular sieve is heated in an oxidizing atmosphere (such as air or oxygen), a neutral atmosphere (such as nitrogen or other inert gases), or a reducing atmosphere (such as hydrogen). The atmosphere can be dry or contain water.

[0044] The temperature used for calcination depends on the composition of the material to be calcined and is generally 400° C. to 900° C. for a duration of about 1 to 8 hours. In some cases, calcination can be carried out at a temperature as high as 1200° C. In applications involving the methods described herein, calcination is generally performed at a temperature of 400° C. to 700° C. for about 1 to 8 hours, preferably at a temperature of 400° C. to 650° C. for about 1 to 4 hours.

[0045] In its as-synthesized or calcined form, Al-CIT-13 may have a (SiO 2 +GeO 2 ) / Al 2 O 3 In some aspects, SiO 2 / GeO 2 The molar ratio may be in the range of 3.8 to 6.0 (eg, 3.8 to 5.4, or 3.8 to 5.0, or 4.0 to 6.0, or 4.0 to 5.0).

[0046] As taught in U.S. Patent Application Publication No. 2016 / 0346771, molecular sieve CIT-13 may be described as having a powder XRD pattern exhibiting at least five characteristic peaks at 6.45 (± 0.2), 7.18 (± 0.2), 12.85 (± 0.2), 18.26 (± 0.2), 18.36 (± 0.2), 18.63 (± 0.2), 20.78 (± 0.2), 21.55 (± 0.2), 23.36 (± 0.2), 24.55 (± 0.2), 26.01 (± 0.2) and 26.68 (± 0.2) degrees 2-θ. In some aspects, the molecular sieve may exhibit six, seven, eight, nine or ten such characteristic peaks. The powder XRD pattern presented is determined by standard techniques. The radiation is K-α / doublet of copper. Small variations in the diffraction pattern values ​​in the tables or figures may also result from variations in the organic compounds used in the preparation and from variations in the silica to alumina molar ratio between samples. Despite these small perturbations, the basic crystal structure remains essentially unchanged under the initial preparation and calcination conditions.

[0047] Synthesis of Aluminum Germanium Silicate CIT-15 (Al-CIT-15)

[0048] If desired, calcined Al-CIT-13 prepared as described herein can be converted to aluminum germanosilicate CIT-15 molecular sieve (Al-CIT-15).

[0049] The Al-CIT-13 molecular sieve may be treated with water to degermanate at least a portion of the molecular sieve to produce a phyllosilicate.

[0050] Preferably, the water does not contain inorganic acids, organic acids or their salts. Examples of inorganic acids include hydrochloric acid, nitric acid, sulfuric acid and phosphoric acid. Examples of organic acids include oxalic acid, formic acid, acetic acid and propionic acid. Preferably, the water does not contain inorganic bases, organic bases or their salts. Examples of inorganic bases include ammonia and alkali metal or alkaline earth metal hydroxides and carbonates. Examples of organic bases include organic amines. It is very important to use water for degermaniation because acids or bases can cause the CIT-13 molecular sieve to dealuminate, which may have a negative impact on the active catalytic characteristics of the resulting product.

[0051] The resulting phyllosilicate can be described as a two-dimensional material comprising silicon-rich CFI layers resulting from CIT-13 delamination, wherein the germanium-rich D4R units are removed by hydrolysis, while correspondingly introducing surface silanol (Si-OH) groups. The resulting phyllosilicate can also be described as an aluminogermanosilicate composition consisting primarily of siloxylated silicon-rich CFI layers (of the CIT-13 framework). Without intending to be bound by any theory, it is believed that the transformations described herein generally retain the structure of these silicon-rich CFI layers, and that the starting material and the final product differ in the manner in which these silicon-rich CFI layers are connected to each other.

[0052] These phyllosilicates may be characterized by a major peak in the powder XRD pattern in the range of about 6.9 to about 9 degrees 2-θ, for example in the range of 7.0 (± 0.2) to 8.1 (± 0.2) degrees 2-θ. The angle of this major peak is higher than the corresponding major peak in the Al-CIT-13 molecular sieve from which it is derived. This shift to higher 2-θ angles in the phyllosilicates is consistent with the removal of d4r building blocks and the tighter packing of the silicon-rich cfi layers. Some differences may appear in the absolute position of this major peak. This can be explained when one realizes that the peak is attributed to a single layer of the stack (i.e., each layer is not sufficient to provide a diffraction pattern) and that the diffraction pattern can only be seen by stacking multiple phyllosilicates. In this case, the stacking appears to be extremely sensitive to trace amounts of intercalated impurities (e.g., water) that may be present between the phyllosilicate layers, which would affect the stacking and therefore the position of the diffraction peak. Additionally or alternatively, different levels of silanol side chains may affect the stacking distance. In any case, the d spacing of the stacked layers is between to within the range.

[0053] The phyllosilicate may have a SiO of at least 25 (e.g., 25 to 200, or 25 to 100, or 25 to 80, or 25 to 60, or 50 to 200, or 50 to 100, or 50 to 80, or 50 to 60). 2 / GeO 2 Additionally or alternatively, the phyllosilicate may have a SiO ratio of at least 50 (e.g., 50 to 1000, or 50 to 800, or 100 to 1000, or 100 to 800, or 200 to 1000, or 225 to 800). 2 / Al 2 O 3 Molar ratio.

[0054] The temperature can be about 20°C to 180°C (e.g., 50°C to 100°C, or 60°C to 100°C, or 70°C to 100°C, or 80°C to 100°C). ℃ to 100°C, or 90°C to 100°C) in water-treated Al-CIT-13 molecular sieve.

[0055] The Al-CIT-13 molecular sieve may be treated with water for a duration ranging from 30 minutes to 72 hours (eg, 6 to 36 hours, or 18 to 30 hours).

[0056] The weight ratio of water to Al-CIT-13 during treatment can range from 2: 1 to 500: 1 or more (e.g., 5: 1 to 500: 1, or 10: 1 to 500: 1, or 50: 1 to 500: 1, 100: 1 to 500, or 2: 1 to 300: 1, or 5: 1 to 300: 1, or 10: 1 to 300: 1, or 50: 1 to 300: 1, or 100: 1 to 300: 1).

[0057] After treating Al-CIT-13 with water, the resulting phyllosilicate can be separated from the suspension. There are no specific restrictions on suitable separation methods, and every solid-liquid separation technique is conceivable. Suitable separation methods include filtration (such as suction filtration or pressure filtration), centrifugation and rapid drying (such as spray drying or spray granulation).

[0058] The recovered phyllosilicate can be subjected to a washing step and / or dried.

[0059] Any conceivable cleaning agent can be used. Usable cleaning agents include water, alcohols (e.g. methanol, ethanol, propanol) or mixtures thereof. Preference is given to water or a mixture of water and at least one alcohol, preferably water and ethanol, with water being particularly preferred as the cleaning agent. If washing is applied, the washing process is preferably continued until the conductivity of the washing water reaches at most 1000 μS / cm (e.g. at most 850 μS / cm, or at most 700 μS / cm).

[0060] Suitable drying methods include conventional drying in an oven (intermittent or continuous drying process), rapid drying (such as spray drying or spray granulation), flash drying or microwave drying. Drying can be carried out at a temperature in the range of about 20°C to 200°C (e.g., 80°C to 190°C or 100°C to 180°C) in a suitable atmosphere (such as industrial nitrogen, air, lean air or vacuum).

[0061] Phyllosilicates are capable of topological rearrangement [(re)organization and (re)assembly] to form CIT-15.

[0062] After Al-CIT-13 is treated with water, the resulting phyllosilicate is calcined. During calcination, the phyllosilicate can undergo a topological rearrangement to form the aluminum germanosilicate CIT-15 molecular sieve.

[0063] Topological rearrangement can occur in layered materials containing terminal silanol groups, such as currently produced phyllosilicates. Upon calcination, these terminal silanol groups condense, thereby releasing water and forming Si-O-Si bonds. Without intending to be bound by any theory, it is believed that the conversion of phyllosilicates to CIT-15 operates through this mechanism.

[0064] The calcining step can be performed at a variety of temperatures and time periods. Typical peak calcining temperatures are generally in the range of 350°C to 925°C or higher (eg, 400°C to 650°C).

[0065] The calcining step may be performed over a period of time ranging from 30 minutes to 48 hours (eg, 1 to 24 hours, or 1 to 12 hours, or 2 to 10 hours, or 3 to 8 hours, or 4 to 6 hours).

[0066] The calcining step can be carried out in a calcining gas stream comprising an inert gas (e.g., nitrogen), oxygen, air, or any mixture or combination thereof. In some aspects, the calcining gas stream can comprise air, while in other aspects, the calcining gas stream can include a mixture of air and nitrogen. However, in certain aspects, the calcining gas stream can be an inert gas, such as nitrogen and / or argon.

[0067] The calcining step can be carried out in any number of well-known apparatuses, including rotary calciners, fluidized bed calciners, batch furnaces, and the like.

[0068] As taught in U.S. Patent Application Publication No. 2017 / 0252729, molecular sieve CIT-15 can be described as having a powder XRD pattern exhibiting at least five characteristic peaks at 8.15 (±0.2), 10.13 (±0.2), 12.80 (±0.2), 16.25 (±0.2), 19.03 (±0.2), 19.97 (±0.2), 20.33 (±0.2), 23.79 (±0.2), 23.91 (±0.2), 24.10 (±0.2), 24.63 (±0.2), 25.77 (±0.2), 26.41 (±0.2), 27.75 (±0.2), 34.7 (±0.2) and 37.78 (±0.2) degrees 2-θ. In separate embodiments, the molecular sieve may exhibit six, seven, eight, nine or ten such characteristic peaks.

[0069] The Al-CIT-15 molecular sieve of the present invention may have a SiO content of at least 25 (e.g., 25 to 100, or 25 to 80, or 25 to 60, or 40 to 100, or 40 to 80, or 40 to 60). 2 / GeO 2 Additionally or alternatively, the Al-CIT-15 molecular sieve may have a SiO content of at least 50 (e.g., 50 to 500, or 50 to 200, or 100 to 500, or 100 to 200). 2 / Al 2 O 3 Molar ratio.

[0070] Example

[0071] The following illustrative examples are intended to be non-limiting.

[0072] Example 1

[0073] Synthesis of Al-CIT-13

[0074] 9.9 g of 1,2-dimethyl-3-(3-methylbenzyl)imidazolium hydroxide (Q-OH) solution (19.4% solution) was added to a 23 mL Teflon liner. 0.37 g of germanium oxide was added and the mixture was stirred until clear. 2.75 g of NALCOWater aluminosilicate sol (SAR=131; 31.2% silica-alumina solids in water) was added. Excess water was evaporated by gently blowing a nitrogen stream over the top of the liner and the water content was adjusted appropriately. 0.37 g of hydrofluoric acid (48%) was then added. Finally, 0.03 g of germanosilicate CIT-13 seeds were added.

[0075] The final molar ratio of the gel is as follows: 1SiO 2 :0.0076Al 2 O 3 :0.25GeO 2 :0.625Q-OH:0.625HF:12.5H 2 O.

[0076] The liner was transferred to a stainless steel autoclave and the autoclave was placed in an oven at 160°C and rotated at 43 rpm for 14 days. The solid product was washed with excess deionized water and dried in an oven at 95°C.

[0077] The dried product was analyzed by powder XRD and SEM. Figure 1 The SEM image is depicted in Figure 2 and shows a uniform crystal field.

[0078] The initial synthesis product has 130 SiO 2 / Al 2 O 3 The molar ratio of SiO 2 / GeO 2 Mole ratios as determined by Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES).

[0079] Example 2

[0080] Calcination of Al-CIT-13

[0081] The pre-synthesized product of Example 1 was calcined in a muffle furnace, heated to 550°C at a rate of 1°C / min under air flow, and kept at 550°C for 5 hours, cooled, and then analyzed by powder XRD. The powder XRD pattern showed that the material remained stable after calcination.

[0082] The calcined product has a SiO 2 / Al 2 O 3 The molar ratio of SiO 2 / GeO 2 Molar ratios as determined by ICP-AES.

[0083] Using N 2 As adsorbent and using the t-plot method, the calcined product was subjected to micropore volume analysis. The material showed a 0.15 cm 3 / g of micropore volume.

[0084] Example 3

[0085] Synthesis of Al-CIT-13

[0086] 8.35 g of 1,2-dimethyl-3-(3-methylbenzyl)imidazolium hydroxide (Q-OH) solution (19.4 wt%) was added to 23 mL liner, then add 0.31 g germanium oxide, and stir the mixture until clear. Then, add 0.05 g aluminum isopropoxide first, followed by 2.50 g tetraethyl orthosilicate. Evaporate the appropriate amounts of ethanol, isopropanol, and water by gently blowing a stream of nitrogen through the top of the liner. When the correct molar ratio is reached, add 0.31 g HF (48 wt % solution) and homogenize the mixture with a spatula. Then, add 0.02 g germanosilicate CIT-13 seeds and homogenize the mixture with a spatula. The molar ratio of the gel is 1SiO 2 :0.01Al 2 O 3 :0.25GeO 2 :0.625Q-OH:0.625HF:12.5H 2 O.

[0087] The liner was then loaded into a stainless steel autoclave and the synthesis was carried out in an oven at 160°C with rotation at 43 rpm for 14 days. The solid product was washed with excess deionized water and dried in an oven at 95°C.

[0088] The recovered product was identified as CIT-13 by powder XRD.

[0089] Example 4

[0090] Synthesis of Al-CIT-13

[0091] 9.09 g of 1,2-dimethyl-3-(3-methylbenzyl)imidazolium hydroxide (Q-OH) solution (19.4 wt%) was added to 23 mL 0.34 g of germanium oxide was then added to the liner and the mixture was stirred until clear. Then, 0.04 g of Reheis F2000 aluminum hydroxide (50% Al 2 O 3 ), followed by 2.75 g of tetraethyl orthosilicate. The appropriate amount of ethanol and water was evaporated by gently blowing a stream of nitrogen through the top of the liner. When the correct molar ratio was reached, 0.34 g of HF (48 wt. % solution) was added and the mixture was homogenized with a spatula. Then, 0.02 g of germanosilicate CIT-13 seed crystals were added and the mixture was homogenized with a spatula. The molar ratio of the gel was 1SiO 2 :0.01Al 2 O 3 :0.25GeO 2 :0.625Q-OH:0.625HF 12.5H 2 O.

[0092] The liner was then loaded into a stainless steel autoclave and the synthesis was carried out in an oven at 160°C with rotation at 43 rpm for 14 days. The solid product was washed with excess water and dried in an oven at 95°C.

[0093] The recovered product was identified as CIT-13 by powder XRD.

[0094] Example 5

[0095] Synthesis of Al-CIT-15

[0096] 0.1 g of the calcined Al-CIT-13 sample from Example 2 was added to 25 g of deionized water in a Teflon-lined FEP bottle. A magnetic stir bar was added and the mixture was stirred in a 95°C oil bath for 24 hours. The mixture was then centrifuged at 15,000 rpm and the liquid was decanted. The solid product was dried in a vacuum oven at room temperature overnight.

[0097] The dried product was then calcined as described in Example 2.

[0098] The calcined product was analyzed by powder XRD and SEM. Figure 3 The SEM image is depicted in Figure 4 and shows a uniform crystal field.

[0099] The calcined product has a SiO 2 / Al 2 O 3 The molar ratio of SiO is 5:1 2 / GeO 2 Molar ratios as determined by ICP-AES.

[0100] Using N 2 The calcined product was analyzed for micropore volume using the t-plot method as the adsorbent. The molecular sieve showed a pore volume of 0.03 cm 3 / g of micropore volume.

[0101] The acid site density of the calcined product was characterized by temperature-programmed desorption using n-propylamine and found to be 28 μmol H + / g.

[0102] Example 6

[0103] Catalyst preparation

[0104] Al-CIT-15 prepared according to Example 5 was ion exchanged in an aqueous solution of palladium nitrate having a pH of about 10 and a Pd loading of 0.5 wt%. The Pd exchanged zeolite was washed with deionized water to a conductivity of less than 50 μS / cm and dried. The zeolite was then calcined in air at 482°C for 3 hours.

[0105] Example 7

[0106] Hydrogenation conversion of n-decane

[0107] For catalytic testing, 0.5 g of the Pd catalyst of Example 6 (the weight of the dehydrated sample was determined by thermogravimetric analysis at 600° C.) was loaded into the center of a 23-inch long×0.25-inch outer diameter stainless steel reactor tube, and corundum was loaded upstream of the catalyst for preheating the feed (total pressure was 1200 psig; the downward flowing hydrogen rate was 12.5 mL / min when measured at 1 atmosphere and 25° C.; and the downward flowing liquid feed rate was 1 mL / h). The catalyst was first reduced in flowing hydrogen at 315° C. for 1 hour. The reaction was carried out at a temperature of 500° F. to 650° F. The products were analyzed by online capillary gas chromatography (GC) approximately every sixty minutes. The raw data from the GC was collected by an automatic data collection / processing system, and the hydrocarbon conversion was calculated from the raw data. The conversion is defined as the amount of n-decane (in mole %) that reacts to produce other products (including iso-C10). The yield of iso-C10 is expressed as the mole percentage of products other than n-decane. The yield of cracked products (less than C10) is expressed as the mole percentage of n-decane converted to cracked products. Figures 5 to 7The results show that the isomerization performance of Al-CIT-15 is good.

Claims

1. A method for synthesizing aluminum germanium silicate molecular sieve CIT-13, the method include: (1) preparing a reaction mixture, the reaction mixture comprising: (a) aluminum source; (b) a silicon source; (c) a germanium source; (d) an organic structure directing agent (Q), the organic structure directing agent comprising one or more of a 1,2-dimethyl-3-(3-methylbenzyl)imidazolium cation, a 1-methyl-3-(3-methylbenzyl)imidazolium cation, a 1,2-dimethyl-3-(3,5-dimethylbenzyl)imidazolium cation and a 1-methyl-3-(3,5-dimethylbenzyl)imidazolium cation; (e) a fluoride ion source; (f) water; and (g) a seed material, wherein the seed material comprises a crystalline molecular sieve of a *CTH framework type; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the aluminum germanosilicate molecular sieve.

2. The method of claim 1, wherein the reaction mixture has the following molar ratio composition:

3. The method of claim 1, wherein the reaction mixture has the following molar ratio composition:

4. The method of claim 1, wherein the aluminum source is selected from the group consisting of hydrated aluminum oxide, aluminum hydroxide, alkali metal aluminates, aluminum alkoxides, and water-soluble aluminum salts, and any combination thereof.

5. The method of claim 1, wherein the silicon source is selected from the group consisting of colloidal silica, fumed silica, tetraalkyl orthosilicates, alkali metal silicates, precipitated silica, and any combination thereof.

6. The method of claim 1, wherein both the aluminum source and the silicon source are aluminosilicate sols.

7. The method of claim 1, wherein the germanium source is selected from the group consisting of germanium oxide, germanium nitrate, tetraalkoxygermanium compounds, and any combination thereof.

8. The method of claim 1, wherein the silicon source and the germanium source are in the range of 1 to 10 SiO 2 / GeO 2 Mole ratio exists.

9. The method of claim 1, wherein the seed material comprises a molecular sieve selected from the group consisting of CIT-13, NUD-2, SAZ-1, and any combination thereof.

10. The method of claim 1, wherein the seed material is present in an amount of 0.1% to 10% by weight of the silica in the reaction mixture.

11. The method of claim 1, wherein the crystallization conditions include a temperature of 100°C to 200°C and a crystallization time of about 1 day to 21 days.

12. A method for synthesizing aluminum germanium silicate molecular sieve CIT-15, the method The following steps are involved: (1) preparing a reaction mixture, the reaction mixture comprising: (a) aluminum source; (b) a silicon source; (c) a germanium source; (d) an organic structure directing agent (Q), the organic structure directing agent comprising one or more of a 1,2-dimethyl-3-(3-methylbenzyl)imidazolium cation, a 1-methyl-3-(3-methylbenzyl)imidazolium cation, a 1,2-dimethyl-3-(3,5-dimethylbenzyl)imidazolium cation and a 1-methyl-3-(3,5-dimethylbenzyl)imidazolium cation; (e) a fluoride ion source; (f) water; and (g) a seed material, wherein the seed material comprises a crystalline molecular sieve of a *CTH framework type; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form the aluminum germanosilicate molecular sieve crystals; (3) recovering and calcining the product of step (2) to obtain a calcined aluminum germanium silicate CIT-13 molecular sieve; (4) treating the calcined aluminum germanosilicate CIT-13 molecular sieve with water under conditions sufficient to degermanate at least a portion of the calcined aluminum germanosilicate CIT-13 molecular sieve to obtain a phyllosilicate comprising stratified cfi layers; and (5) recovering and calcining the phyllosilicate under conditions sufficient to convert the phyllosilicate into aluminogermanosilicate CIT-15 molecular sieve.

13. The method of claim 12, wherein the treatment according to step (4) is performed at a temperature of 50°C to 180°C.

14. The method of claim 12, wherein the treatment according to step (4) is performed for 30 minutes to 72 hours.